ANALISIS TINGKAT UNDERPRICING SAHAM PADA PERUSAHAAN YANG MELAKUKAN PENAWARAN SAHAM PERDANA (IPO) DI BEI PERIODE 2012-2016 Studi Kasus Pada Perusahaan Yang Melakukan IPO di Bursa Efek Indonesia Tahun 2012-2016 - Trikosiwi Koco Setyowati; Siti Aisiyah Suciningtyas (Jurnal Ekonomi dan Bisnis, 2018)
The aims of this study is to find out the effect of Profitability, Leverage, against Underpricingto firms at Intial Public Offering (IPO) on Indonesia Stock Exchange 2012-2016 which ismediated by Stock Liqudity. The population in this study are 105 companies at Intial PublicOffering (IPO) that listed on Indonesia Stock Exchange 2012-2016. After selection by using thepurposive sampling method in the population, obtained the results of the census of 71 firmswere through underpricing used as samples. The secondary data collection method that usedis documentation method and indirect observation. Data analysis technique used regressionanalysis of panel data. Based on the results of research, Based on the results of the research,partially profitability has a positive effect to stock liquidity. Leverage has negative and nosignificant effect to stock liquidity. Profitability, Leverage, and Stock Liquidity have a significantnegative effect on underpricing. And simultaneously, Profitability, Leverage, and Stock Liquidityhave an effect on Underpricing.Keywords: Profitabilty, Leverage, Stock Liquidity, Underpricing